Global engagement lowers investment gaps in renewable energy deployment - Guan, Yusheng; An, Kangxin; Zheng, Xinzhu; Zhang, Shihui; Wang, Can (iScience, 2025)
In recent years, the costs of renewable technologies like photovoltaic (PV) and wind power have declined sharply, with scale growth being a key driver. The impact of scale growth comes from both domestic expansion (national endeavor [NE]) and international deployment (global engagement [GE]). Using learning curve models and counterfactual inference, we quantify their respective contributions to the decline in total installed cost of wind and PV power. Results show that GE accounts for 17% of the global cost decline in PV and 48% in wind power. NE plays a dominant role in manufacturing countries such as China, India, and the US, while GE is essential for supporting energy transitions in countries outside these hubs. Without GE, the global investment gap would increase by 42% to meet the 2030 Tripling Target for renewable energy. These findings underscore the critical importance of global cooperation in enabling green and low-carbon development worldwide. [Display omitted] •Global engagement contributed 17% and 48% for solar and wind cost reductions•Global investment gap in renewables would rise by 42% without global engagement•National endeavor plays a critical role in cost reductions in manufacturing countries•Global engagement plays a crucial role in cost savings in lower income countries Energy resources; Energy engineering; Energy sustainability